Applied theatre : creating transformative encounters in the community - Taylor, Philip (Portsmouth, NH : Heinemann, 2003)
Applied theatre is both a term and a movement that's gathering momentum. The movement springs from the desire to change or transform human behavior through the medium of theatre. In this book, Philip Taylor offers strategies for using theatre to raise awareness, propose alternatives, provide healing, and implement community change. As he demonstrates, applied theatre teaches us to teach others, helps communities deal with issues, and gives voice to the views of the silent and the marginal. In numerous examples, Taylor shows exactly how the theatrical art form is being harnessed to help communities question aspects of who they are and what they aspire to be.
Bibliografija: str. 133-137
Keywords: Theater and society; Community theater; kazalište i društvo; kazalište u zajednici; primjenjeno kazalište